Exploration of transcultural properties of the reduced version of the Morningness-Eveningness Questionnaire (rMEQ) using adaptive neuro-fuzzy inference system - Biswas, Animesh; Adan, Ana; Haldar, Prasun; Majumder, Debasish; Natale, Vincenzo; Randler, Christoph; Tonetti, Lorenzo; Sahu, Subhashis (Biological rhythm research, 2014)
The reduced version of the Morningness-Eveningness Questionnaire (rMEQ) is widely used to study morningness orientation. The fuzzy analysis helps mapping outputs of the questionnaire irrespective of linguistic and cross-cultural aspects in an efficient manner. In the present study, the rMEQ was administered to a convenience sample of university students (N = 2660) in four different countries and responses have been quantified by using an adaptive neuro-fuzzy inference system for the cross-cultural comparison and then the quantified values are used to construct the proposed model. The cross-country fuzzy morningness value showed that environmental temperature has definite influence on morningness orientation but other factors may also have a role. The developed model can be universally used to analyse the morning-evening orientation of people more precisely without cross-language and cross-cultural biases and it would become a potential tool for interpretation of morningness scores and counselling of individuals.